The Relationship Between the Ability to Read Qur’an and Interest in Learning Arabic Students - Riris Tarisun Nisak (Journal of Practice Learning and Educational Development, 2026)
Arabic indeed holds a strategic position in the constellation of Islamic education; however, the responsiveness of MTs Al-Hidayah Karanggupito Ngawi students toward learning Arabic still shows a relatively low tendency, even tho they have adequate Al-Qur'an literacy competence. This study aims to examine the relationship between the ability to read the Quran and the educational interest in the Arabic language among the student population. The methodology applied is a correlational quantitative approach with the implementation of saturated sampling techniques on all 50 students as research subjects. Data collection was carried out using the Al-Qur'an recitation practice test instrument and a Likert-scale learning interest questionnaire that had undergone a validation process. Data analysis was conducted using the Pearson Product Moment correlation test after the normality and linearity requirements were met. The research findings show a correlation coefficient value of r = 0.221, which is lower than the r-table (0.279) at a 5% significance level, thus H₀ is not rejected. In conclusion, no statistically significant relationship was found between the ability to read the Al-Qur'an and students' interest in learning Arabic. The implications of these results indicate that interest in Arabic education is more determined by complex affective factors, including intrinsic motivation, pedagogical methodology, and contextual environmental support. Therefore, it is necessary to develop learning strategies that explicitly integrate Quran reading practices with the substance of Arabic language material.